2012
DOI: 10.1103/physrevb.86.115306
|View full text |Cite
|
Sign up to set email alerts
|

Influence of doping on the photoactive properties of magnetron-sputtered titania coatings: Experimental and theoretical study

Abstract: The UCD community has made this article openly available. Please share how this access benefits you. Your story matters! (@ucd_oa) Some rights reserved. For more information, please see the item record link above. PHYSICAL REVIEW B 86, 115306 (2012) Influence of doping on the photoactive properties of magnetron-sputtered titania coatings:Experimental and theoretical study Titanium dioxide (TiO 2 ) thin films, doped with chromium (Cr) and codoped with chromium-carbon (Cr, C) and chromium-nitrogen (Cr, N) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 56 publications
2
38
0
Order By: Relevance
“…McDonnell et al [34], both with an exact-exchange contribution of 25%. However, in this study we "tune" the exact-exchange contribution parameter "α" in eqn.…”
Section: Theoreticalmentioning
confidence: 98%
See 1 more Smart Citation
“…McDonnell et al [34], both with an exact-exchange contribution of 25%. However, in this study we "tune" the exact-exchange contribution parameter "α" in eqn.…”
Section: Theoreticalmentioning
confidence: 98%
“…PBEsol has been used due to its superior geometry prediction vis-à-vis PBE exchange-correlation in solids [32,33] leading to more accurate Born-Oppenheimer forces acting on the electronic wave-functions, and providing the best feasible estimation of electronic properties. To avoid the expensive calculation of long-range HF exchange, this term is replaced by long-range PBEsol exchange; details are inferred in the earlier work [34].…”
Section: Theoreticalmentioning
confidence: 99%
“…PBEsol has been used due to its superior geometry prediction vis-à-vis PBE exchange-correlation in solids [21,22] leading to more accurate Born-Oppenheimer forces acting on the electronic wave-functions, and providing the best feasible estimation of electronic properties. To avoid the expensive calculation of long-range HF exchange, this term is replaced by long-range PBEsol exchange; further details may be obtained from earlier work applied to photovoltaic properties of titania [23]. In any event, this choice of parameters for HSE06-PBEsol is identical to the recent work of Schimka et al [24], who have found that this works well for a range of solids, and also of McDonnell et al [23], both with an exactexchange contribution of 25%.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…To avoid the expensive calculation of long-range HF exchange, this term is replaced by long-range PBEsol exchange; further details may be obtained from earlier work applied to photovoltaic properties of titania [23]. In any event, this choice of parameters for HSE06-PBEsol is identical to the recent work of Schimka et al [24], who have found that this works well for a range of solids, and also of McDonnell et al [23], both with an exactexchange contribution of 25%. However, it is also possible to change the proportion of exact exchange to tailor the band-gap and optical properties for optimal agreement with experiment; for instance, 10% proportions were used in recent work for bismuth-containing compounds [25,26].…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…Hydrogen, boron, carbon, nitrogen, fluorine, iodine, sulfur, and phosphorus have been used in this capacity, but nitrogen has been studied most extensively. Until now, various approaches to incorporate nitrogen atoms into titania have been reported, such as doping during film sputtering [131], annealing under ammonia gas [12], ion implantation [132,133], hydrazine treatment [134][135][136], urea treatment [137][138][139], treatment of sol-gel titania with nitrogen-containing organics [140], electrochemical processing [141], chemical vapor deposition [142], and plasma techniques [11,13,35,[143][144][145][146][147][148][149][150]. Most of the above doping methods require high temperature treatment and complicated or expensive equipment.…”
Section: Nitrogen Dopingmentioning
confidence: 99%